Effect of integrating postpartum family planning into the health extension program in Ethiopia on postpartum adoption of modern contraception. (2020) - Sitrin, Deborah; Jima, Gebi H; Pfitzer, Anne; Wondimu, China; Belete, Tigist Worku; Pleah, Tsigue; Assefa, Berhane; Kebede, Tenaye; Regassa, Efrem; Usman, Ezedin Aman; Ahmed, Saifuddin
No abstract available